Identification of psychometric properties of acculturative stress scale for international students - Karyanta, Nugraha Arif; Suryanto, Suryanto; Matulessy, Andik (Jurnal Ilmiah Psikologi Terapan, 2024)
Ensuring reliable measurement instruments is crucial for psychologists and practitioners. The Acculturative Stress Scale for International Students (ASSIS) is a widely used tool for assessing acculturative stress. An analysis of data from 100 international students in Indonesia demonstrated that the ASSIS met reliability standards, with AVE values between 0.50 and 0.63 and CR values between 0.73 and 0.91. The ASSIS also satisfied the criteria for content and construct validity. Additionally, the factorial validity of the ASSIS-1 CFA model met 5 out of 6 criteria, including RMSEA < 0.08, SRMR < 0.10, and NFI, CFI, and GFI values > 0.90, while the ASSIS-2 CFA model fulfilled all 6 criteria. Consequently, it can be concluded that the ASSIS is a valid and reliable tool for international students in the Indonesian cultural context.